1996
DOI: 10.1046/j.1365-2249.1996.d01-747.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunoregulation in onchocerciasis: predominance of Th1-type responsiveness to low molecular weight antigens of Onchocerca volvulus in exposed individuals without microfilaridermia and clinical disease

Abstract: SUMMARYChronic and generalized onchocerciasis is associated with suppression of the parasite-specific cellular responsiveness, while exposed individuals without parasitological and clinical evidence of infection (endemic normals) display prominent cellular reactivity to Onchocerca volvulus antigens (OvAg). In order to identify those parasite antigens which may account for this differential cellular responsiveness, total adult worm-derived OvAg were fractionated by means of preparative SDS-PAGE and blot-elution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 21 publications
2
25
1
Order By: Relevance
“…In contrast, in lepromatous patients 748 CSERNOK ET AL who manifest disseminated infection, the T cells respond weakly to M leprae, and the lesions express the Th2 cytokines typical of humoral responses, which include autoreactivity as ANCA production, as has been found in lepromatous leprosy, but not in tuberculoid leprosy (29). In addition, in onchocerciasis the majority of patients demonstrate a vigorous Th1 cellular response, whereas in hyperreactive onchocerciasis (Sowda) autoantibodies to defensin (ANCA) occur (30)(31)(32)(33). WG and MPA are mainly differentiated by the occurrence of granulomatous inflammation, which is present in the former and absent in the latter (1).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in lepromatous patients 748 CSERNOK ET AL who manifest disseminated infection, the T cells respond weakly to M leprae, and the lesions express the Th2 cytokines typical of humoral responses, which include autoreactivity as ANCA production, as has been found in lepromatous leprosy, but not in tuberculoid leprosy (29). In addition, in onchocerciasis the majority of patients demonstrate a vigorous Th1 cellular response, whereas in hyperreactive onchocerciasis (Sowda) autoantibodies to defensin (ANCA) occur (30)(31)(32)(33). WG and MPA are mainly differentiated by the occurrence of granulomatous inflammation, which is present in the former and absent in the latter (1).…”
Section: Discussionmentioning
confidence: 99%
“…Although this has not been observed in all studies (6), it raises the possibility that PC on ES could be a contributor to the IL-10 production. Elevated spontaneous and parasite antigeninduced IL-10 production has also been detected in onchocerciasis patients relative to healthy subjects in areas of endemicity (17), although the PC-ES status of these individuals was not investigated. Elevated spontaneous levels of IL-10, by downregulating Th1 responses, could contribute to the Th2 phenotype often observed in the specific immune response of microfilaria-positive lymphatic filariasis and onchocerciasis patients (19,20).…”
Section: Il-4r␣mentioning
confidence: 99%
“…The notion was supported by experimental data showing production of the characteristic Th1 marker interferon (IFN)-g [3, 7, 10]. The findings, however, were not always consistent [7,[10][11][12], and it was concluded that the classical Th1/Th2 dichotomy might not be applicable to O. volvulus and other filarial infections [11,13]. In this study, we assessed cell proliferation and cytokine production in response to O. volvulus antigen in whole-blood cultures from several hundred O. volvulusexposed persons.…”
mentioning
confidence: 99%